A nexus perspective on competing land demands: Wider lessons from a UK policy case study. Issue 59 (May 2016) - Sharmina, Maria; Hoolohan, Claire; Bows-Larkin, Alice; Burgess, Paul J.; Colwill, James; Gilbert, Paul; Howard, David; Knox, Jerry; Anderson, Kevin
Highlights: Interdependencies at water–energy–food nexus are largely ignored in decision-making. A radical overhaul of the current system of policy- and decision-making is needed. A new modelling framework needs to reconcile competing demands for resources. To achieve resilience at the nexus, ecosystems services have to be viewed as a whole. Non-monetary, physical-unit constraints on ecosystem services need to be valued. Abstract: As nations develop policies for low-carbon transitions, conflicts with existing policies and planning tools are leading to competing demands for land and other resources. This raises fundamental questions over how multiple demands can best be managed. Taking the UK as an empirical example, this paper critiques current policies and practices to explore the interdependencies at the water-energy-food nexus. It considers how current land uses and related policies affect the UK's resilience to climate change, setting out an agenda for research and practice relevant to stakeholders in land-use management, policy and modelling. Despite recent progress in recognising such nexus challenges, most UK land-related policies and associated science continue to be compartmentalised by both scale and sector and seldom acknowledge nexus interconnections. On a temporal level, the absence of an over-arching strategy leaves inter-generational trade-offs poorly considered. Given the system lock-in and the lengthy policy-making process, it is essential to develop alternative ways of providing dynamic, flexible, practical and scientifically robust decision support for policy-makers. A range of ecosystem services need to be valued and integrated into a resilient land-use strategy, including the introduction of non-monetary, physical-unit constraints on the use of particular services.